Dynamic earth [videorecording] - Discovery Channel (Quezon City : MagnaVision, 2005)
Let this fast-paced compilation introduce your elementary learners to Mother Nature in a really bad mood, with dramatic footage of king-size waves, deadly storms, and supercharged skies. In four fascinating segments, your students will be blown away by the awesome power of the Earth.
Science : Grade level 3-6
Keywords: Planet earth; Forces of nature